MOLECULAR DIVERSITY ANALYSIS AND SEX DETERMINATION IN PAPAYA (CARICA PAPAYA L.) USING MOLECULAR MARKERS - P. SHIVKUMAR; P. SHAMPRASAD; B. ROHINI (The Bioscan, 2014)
A total of twenty simple sequence repeat (SSR) primers were used to understand the genetic diversity between seven Indian papaya (Carica papaya L.) cultivars. The SSRs produced amplicons in all the genotypes. A total of 42 alleles were detected from these primers. Sixteen primers were polymorphic with average polymorphic percentage of eighty.The similarity coefficient ranged from 0.33 to 1.00 and was minimum (33 %) between Arka Prabhat and Co-5 and divided the genotypes into two broad clusters in a dendrogram. ArkaPrabhat, Honey Dew, Red Lady grouped into subcluster I and Solo and Arka Surya in subcluster II in main cluster I while Co-2 and Co-5 varieties were in main cluster II.The RAPD-SCAR marker OP-Y7 developed for the sex determination of Colombian papaya varieties amplified a 369 bp fragment in male plants of all the Indian cultivars except female plants of Co-2. Diversity in papaya cultivars needs to be exploited for developing superior cultivars for characteristics like better fruit quality and disease resistance. SCAR marker for sex determination will probably aid papaya cultivation and breeding by saving time, space and labor cost otherwise which is required to grow plants of undesirable sex and will be useful to the farmer and is of commercial value.